Penerapan Bimbingan Kelompok Untuk Meningkatkan Solidaritas Antar Sesama Lansia - Nandini Faradillah Putri; Komaruddin Komaruddin; Manah Rasmanah (Journal of Society Counseling, 2023)
This research is entitled "Implementation of Group Guidance to Increase Solidarity among Fellow Elderly at Harapan Kita Palembang Social Institution". This research is important because the elderly at the Harapan Kita Social Home for the Elderly are far from their families and relatives, as well as limited human or labor resources at the Harapan Kita Social Home for the Elderly, so being together, needing each other, and helping each other are very important for elderly. Therefore, this solidarity is needed to help the elderly so that they can help each other so that it can ease the daily activities of the elderly. The aim is to determine the level of solidarity among the elderly and the application of group guidance to increase solidarity among the elderly. This type of research is field research with descriptive qualitative research methods. The subjects of this study were employees or staff and the elderly living in the Harapan Kita Palembang Social Home. Data collection techniques in this study are observation, interviews, and documentation. Data analysis techniques use data analysis techniques from Miles and Huberman, namely there are three types of activities, namely data reduction (Data Reduction), Data Display (Data Display) and Drawing Conclusions (Verification). The results of this study are that the solidarity before giving group guidance to the elderly is quite low, which are marked by lack of a strong friendship and brotherhood or sisterhood, but after giving group guidance increase in a sense of solidarity among others and is quite kind to oder elderly. The application of group guidance is carried out with 3 meetings which are carried out with 4 stages of group guidance. After being given group guidance, the solidarity of the elderly has begun to be seen in terms of its delivery to other elderly people, such as wanting to provide small assistance to other elderly people when they see that the elderly are having difficulties.